1970
DOI: 10.1016/s0006-3495(70)86352-4
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Electrical Interaction of Cardiac Cells

Abstract: A model of the electrical activity of excitable membrane was used to simulate action potential propagation in cardiac cells. Using an implicit method for solving finite difference equations, propagation through the intercalated disc region between two abutting cells was studied. A model of interaction was constructed and parameters of the cellular junction determined. Estimates of the intercalated disc resistance were then made from these junction parameters using a field analysis of the junction. Values of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1972
1972
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(18 citation statements)
references
References 6 publications
2
16
0
Order By: Relevance
“…The value he calculated for specific disc resistance (3 ~ cm 2) compares very well with that predicted by Woodbury and Crill (1961) on the basis of a potential field analysis of the gap between the membrane regions forming the intercalated disc. Heppner and Plonsey (1970) confirmed their results. Similar values were found by Tanaka and Sasaki (1966) and Spira (1971).…”
supporting
confidence: 81%
“…The value he calculated for specific disc resistance (3 ~ cm 2) compares very well with that predicted by Woodbury and Crill (1961) on the basis of a potential field analysis of the gap between the membrane regions forming the intercalated disc. Heppner and Plonsey (1970) confirmed their results. Similar values were found by Tanaka and Sasaki (1966) and Spira (1971).…”
supporting
confidence: 81%
“…Several investigators adopted a segmented model consisting of two cellular domains with excitable membranes connected by a single resistance. 32 - 34 Lieberman et aJ, 33 using linear cables as cellular domains, reported a ratio of TJR^ of 6 as an upper limit for successful impulse transfer. Employing single cells as cellular domains, Joyner and van Capelle 36 found that the requirement of successful transmission was met with ratios of r^R;,, in the range of 1.7-10.…”
Section: Impulse Transfer and Nexal Resistancementioning
confidence: 99%
“…The length constant A, i.e., the distance over which the subthreshold voltage pulse decreases by a factor e, differs in various parts of the heart (Table I) but is generally reported in the range 0.5-1.5 mm (Spira, 1971 ;Weidmann, 1970;Bonke, 1973a,b;Seyama, 1976). When combined with measurements of junctional area, the junctional resistance between myocardial cells has been estimated at less than 5 Ω · c m 2 (Woodbury and Crill, 1961;Heppner and Plonsey, 1970;Matter, 1973). Measured values of longitudinal resistivity in myocardial fibers (Table I, K,) generally fall in the range of 100-500 Ω · cm.…”
Section: Cell Junctionsmentioning
confidence: 99%